Fabrication of Hybrid Organic Photovoltaic Devices Using Electrostatic Spray Method - Zhe-Wei Chiu; Yu-Jen Hsiao; Te-Hua Fang; Liang-Wen Ji (International Journal of Photoenergy)
Hybrid organic photovoltaic devices (OPVDs) are fabricated using the electrostatic spray (e-spray) method and their optical and electrical properties are investigated. E-spray is used to deposit a hybrid film (P3HT: PCBM/nanodiamond) with morphology and optical characteristics onto OPVDs. The root-mean-square roughness and optical absorption increase with increasing nanodiamond content. The performance of e-spray is comparable to that of the spin-coating method under uniform conditions. The device takes advantage of the high current density, power conversion efficiency, and low cost. Nanodiamond improves the short-circuit current density and power conversion efficiency. The best performance was obtained with 1.5 wt% nanodiamond content, with a current density of 7.28 mA/cm2 and a power conversion efficiency of 2.25%.